Discovery and structure activity relationship of the first potent cryptosporidium FIKK kinase inhibitor. Issue 5 (1st March 2017) - Osman, Khan T.; Ye, Juntao; Shi, Zhihao; Toker, Christina; Lovato, Diogo; Jumani, Rajiv S.; Zuercher, William; Huston, Christopher D.; Edwards, Aled M.; Lautens, Mark; Santhakumar, Vijayaratnam; Hui, Raymond
Graphical abstract: Abstract: FIKKs are parasite-specific protein kinases with distinctive sequence motifs and their biological roles have not been completely elucidated. Here, we report the first potent Cryptosporidium FIKK (CpFIKK) inhibitor. We identified4b as a potent (IC50 = 0.2 nM) inhibitor of CpFIKK catalytic activity. In addition, we identified both CpCDPK1 selective as well as dually acting CpFIKK-CDPK1 inhibitors from the same structural class of compounds. We evaluated these CpFIKK inhibitors for inhibition of parasite growth in vitro . The observed effects on parasite growth did not correlate with CpFIKK inhibition, suggesting that CpFIKK may not be involved in parasite growth.